A Single Dose of the DENV-1 Candidate Vaccine rDEN1Δ30 Is Strongly Immunogenic and Induces Resistance to a Second Dose in a Randomized Trial - Durbin, Anna P.; Whitehead, Stephen S.; Shaffer, Donna; Elwood, Dan; Wanionek, Kimberli; Thumar, Bhavin; Blaney, Joseph E.; Murphy, Brian R.; Schmidt, Alexander C. (PLoS neglected tropical diseases, 2011)
Dengue is an emerging infectious disease that has become the most important arboviral infection worldwide. There are four serotypes of dengue virus, DENV-1, DENV-2, DENV-3, and DENV-4, each capable of causing the full spectrum of disease. rDEN1Δ30 is a live attenuated investigational vaccine for the prevention of DENV-1 illness and is also a component of an investigational tetravalent DENV vaccine currently in Phase I evaluation. A single subcutaneous dose of rDEN1Δ30 was previously shown to be safe and immunogenic in healthy adults. In the current randomized placebo-controlled trial, 60 healthy flavivirus-naive adults were randomized to receive 2 doses of rDEN1Δ30 (N = 50) or placebo (N = 10), either on study days 0 and 120 (cohort 1) or 0 and 180 (cohort 2). We sought to evaluate the safety and immunogenicity of this candidate vaccine in 50 additional vaccinees and to test whether the humoral immune response could be boosted by a second dose administered 4 or 6 months after the first dose. The first dose of vaccine was well tolerated, infected 47/50 vaccinees and induced seroconversion in 46/50 vaccinees. Irrespective of dosing interval, the second dose of vaccine was also well tolerated but did not induce any detectable viremia or ≥4-fold rise in serum neutralizing antibody titer.Only five subjects had an anamnestic antibody response detectable by ELISA following a second dose of vaccine, demonstrating that the vaccine induced sterilizing humoral immunity in most vaccinees for at least six months following primary vaccination.The promising safety and immunogenicity profile of this vaccine confirms its suitability for inclusion in a tetravalent dengue vaccine.